Out-of-plane Characterization of Silicon-on-insulator Multiuser MEMS Processes-based Tri-axis Accelerometer - L., Sujatha; S., Kalaiselvi; Vigneswaran, Narayanamurthy (IFSA Publishing, S.L., 2016)
In this paper, we discuss the analysis of out-of-plane characterization of a capacitive tri-axis accelerometer fabricated using SOI MUMPS (Silicon-on Insulator Multi user MEMS Processes) process flow and the results are compared with simulated results. The device is designed with wide operational 3 dB bandwidth suitable for measuring vibrations in industrial applications. The wide operating range is obtained by optimizing serpentine flexures at the four corners of the proof mass. The accelerometer structure was simulated using COMSOL Multiphysics and the displacement sensitivity was observed as 1.2978 nm/g along z-axis. The simulated resonant frequency of the device was found to be 13 kHz along z axis. The dynamic characterization of the fabricated tri-axis accelerometer produces the out-of-plane vibration mode frequency as 13 kHz which is same as the simulated result obtained in z-axis.